Biopolymers: An inclusive review - Great Iruoghene Edo; Winifred Ndudi; AliB.M. Ali; Emad Yousif; Agatha Ngukuran Jikah; Endurance Fegor Isoje; Ufuoma Augustina Igbuku; Alice Njolke Mafe; Rapheal Ajiri Opiti; Chioma Judith Madueke; Arthur Efeoghene Athan Essaghah; Dina S. Ahmed; et al. (Hybrid Advances)
Biopolymers are composed of recurring units of similar or same monomers joined together and are either derived from biological systems or manufactured from biological sources. Been a leading class of functional materials that are apposite for high-value applications, biopolymers are utilized in the food, petroleum, medical and pharmaceutical industries for various purposes. Moreover, naturally occurring biopolymers such as starch, proteins, rubber, cellulose, chitin, RNA, peptides and DNA been biodegradable, were thought of as suitable alternatives to the synthetic ones which came from fossil fuel sources and had adverse environmental effects. Moving forward, many biopolymers have and are still been produced to meet ever increasing demands. This paper presents an all inclusive review of biopolymers, their polymer backbone, impacts on environment, and methods of degradation, uses, chemical modification of biopolymers for the creation of hydrogels used in medicine, economic impact and future outlook.